Advances Toward Engineering Functionally Mature Human Pluripotent Stem Cell-Derived β Cells - Velazco-Cruz, Leonardo; Goedegebuure, Madeleine M.; Millman, Jeffrey R. (Frontiers in Bioengineering and Biotechnology, 2020)
Human stem cell-derived β (SC-β) cells have the potential to revolutionize diabetes treatment through disease modeling, drug screening, and cellular therapy. SC-β cells are likely to represent an early clinical translation of differentiated human pluripotent stem cells (hPSC). In 2014, two groups generated the first in vitro-differentiated glucose-responsive SC-β cells, but their functional maturation at the time was low. This review will discuss recent advances in the engineering of SC-β cells to understand and improve SC-β cell differentiation and functional maturation, particularly new differentiation strategies achieving dynamic glucose-responsive insulin secretion with rapid correction to normoglycemia when transplanted into diabetic mice.